Comparative study of switching strategies for cascaded H-bridge multilevel inverter - Usman Bashir, Tayab (Universiti Malaysia Perlis (UniMAP), 2019)
Multilevel inverters are capable of producing AC staircase output waveform without bulky passive filter. Therefore, among different types of inverters the multilevel inverters are gaining popularity for photovoltaic applications. If the switching angle of every voltage level is not carefully chosen then the total harmonic distortion (THD) of voltage output waveform may become unacceptable. In this project, four switching angle arrangement techniques are applied to a cascaded H-bridge multilevel inverter. The performance of 3-, 5-, 7-, 9-, 11-, 13- and 15-level cascaded H-bridge multilevel inverter with four switching angle arrangement techniques at different power factor loads have been evaluated and compared by using PSIM software. The purpose of evaluating and comparing the simulation results of cascaded H-bridge multilevel inverter with different power factor loads is to analyze the effects of inductive load on the THD of voltage and current. Simulation results show that one of technique is able to generate an output voltage and current waveform with lowest THD whilst one of the power factor loads is also able to produce the output current waveform with lowest THD. In addition, one of the techniques produces output voltage waveform with the highest fundamental voltage component.